Complete plastome sequence of Iodes cirrhosa Turcz., the first in the Icacinaceae, comparative genomic analyses and possible split of Idoes species in response to climate changes - Wang,Liqiang; Zhang,Hui; Jiang,Mei; Chen,Haimei; Huang,Linfang; Liu,Chang (PeerJ, 2019)
Plastome-based phylogenetic study has largely resolved the phylogeny of Icacinaceae. However, no single complete plastome sequence is available for Icacinaceae species, thereby limiting the further phylogenomics analysis of the members of this family. Here, we obtained the complete plastome sequence of Iodes cirrhosa Turcz., which is the first in Icacinaceae, by using the next-generation sequencing technology. The genome was annotated and compared with other closely related plastomes by using mVISTA. The divergence time of six Iodes species was analyzed using the BEAST software. The plastome of I. cirrhosa was 151,994 bp long, with a pair of inverted repeats (IRs, 24,973 bp) separated by a large single-copy (LSC, 84,527 bp) region and a small single-copy (SSC, 17,521 bp) region. The plastome encoded 112 unique genes, including 80 protein-coding, 28 tRNA, and four rRNA genes. Approximately 59 repeat sequences and 188 simple sequence repeats were identified. Four pairs of partially overlapped genes, namely, psbD/psbC, ndhF/Ψycf1, atpB/atpE, and rpl22/rps3, were observed. A comparison of the boundaries of the LSC, SSC, and IR regions with four other plastomes from Aquifoliales and Sapindales exhibited a high overall degree of sequence similarity. Four most highly variable regions, namely, trnH-GUG/psbA, psbM/trnD-GUC, petA/psbJ, and rps16/trnQ-UUG, were found. Using the plastome of I. cirrhosa as reference, we reassembled the plastomes of five Iodes species. Ka/Ks ratio analyses revealed that 27 genes and 52 amino acid residue sites from 11 genes had undergone strong positive selection in the Iodes branch, with the most abundant proteins being the NDH and ribosomal proteins. Divergence-time analysis indicated that Iodes species were first formed 34.40 million years ago. Results revealed that the ancestor of the six species was likely to have split in the late Eocene epoch. In summary, the first complete plastome sequence of I. cirrhosa provided valuable information regarding the evolutionary processes of Iodes species.
Keywords: Iodes cirrhosa Turcz.; Icacinaceae; Plastome; Selective pressure; Phylogenomic analysis